2018
DOI: 10.15405/epsbs.2018.09.8
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Trauma Of Children Of Dysfunctional Families

Abstract: The relevance of the research topic relates to the importance of family influence on the development of children's personality. At the same time certain family problems are seen among the causes of children's psychological trauma. We conducted empiric research to study the nature of children's psychological trauma of dysfunctional families. The following methods were used to achieve our goal: observation; conversations with class teachers and children; parents' survey; testing with the help of the following te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Children who are raised in incomplete or broken families do not have access to the cognitive-behavioural resources that help to become self-sufficient, resulting in inhibited functioning not only in a family environment but also in other areas of life (Błażek, 2014). Children whose family was broken suffer from a higher degree of social anxiety and are characterized by lower cognitive competences (Minullina, 2018). They more often withdraw from social relations, achieve lower results at school, and their parents often point to their behavioural problems (Fagan, Churchill, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Children who are raised in incomplete or broken families do not have access to the cognitive-behavioural resources that help to become self-sufficient, resulting in inhibited functioning not only in a family environment but also in other areas of life (Błażek, 2014). Children whose family was broken suffer from a higher degree of social anxiety and are characterized by lower cognitive competences (Minullina, 2018). They more often withdraw from social relations, achieve lower results at school, and their parents often point to their behavioural problems (Fagan, Churchill, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that predominantly unbalanced parenting is common in dysfunctional families. It was also found that parents in dysfunctional households play an important role in the occurrence of psychological stress in their children (Minullina, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In dysfunctional families, mostly both or one parent exhibits unharmonious, parenting style and behaves in an unpredictable manner resulting in the home environment being unstable [8]. Children as a result are forever on guard because they never know what to expect and when conflict is going to take place.…”
Section: The Impact Of Growing Up In a Dysfunctional Familymentioning
confidence: 99%